2015
DOI: 10.1038/srep11760
|View full text |Cite
|
Sign up to set email alerts
|

Novel ZnO hollow-nanocarriers containing paclitaxel targeting folate-receptors in a malignant pH-microenvironment for effective monitoring and promoting breast tumor regression

Abstract: Low pH in the tumor micromilieu is a recognized pathological feature of cancer. This attribute of cancerous cells has been targeted herein for the controlled release of chemotherapeutics at the tumour site, while sparing healthy tissues. To this end, pH-sensitive, hollow ZnO-nanocarriers loaded with paclitaxel were synthesized and their efficacy studied in breast cancer in vitro and in vivo. The nanocarriers were surface functionalized with folate using click-chemistry to improve targeted uptake by the maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 46 publications
0
34
0
2
Order By: Relevance
“…In our previous study 20 , a series of quaternary Mg-Ca-Sr-Zn alloys were fabricated and the in vitro anti-bacterial property was conducted. Besides, in recent years, quit a few articles 21 22 reported that Zn 2+ selectively induced apoptosis in cancer cells 23 24 . Elevation of Zn 2+ concentration can trigger breakdown of mitochondrial membrane potential, caspase activation and cell apoptosis 25 .…”
mentioning
confidence: 99%
“…In our previous study 20 , a series of quaternary Mg-Ca-Sr-Zn alloys were fabricated and the in vitro anti-bacterial property was conducted. Besides, in recent years, quit a few articles 21 22 reported that Zn 2+ selectively induced apoptosis in cancer cells 23 24 . Elevation of Zn 2+ concentration can trigger breakdown of mitochondrial membrane potential, caspase activation and cell apoptosis 25 .…”
mentioning
confidence: 99%
“…Similar results of alumina nanostructure localization were obtained after incubation with L929 fibroblasts (data are not displayed). Thus, the synthesized nanostructures in the medium aggregate and cannot penetrate into the cell [31][32][33][34]. Their toxic effect is first of all related to changes in the cell microenvironment and interaction with the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…With an increase of the incubation time, the percentage of Annexin V(+) PI(+) cells increased, indicating the occurrence of late apoptosis. As mentioned above, the development of apoptosis in cells under the influence of metal ions can be due to a change in the mitochondrial membrane potential, activation of the caspase cycle, and suppression of MAPK activation . In addition, among the main triggers of cell apoptosis include oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that Mg–1Ca–0.5Sr– x Zn ( x = 0, 2, 4, 6 mass %) alloys inhibit the proliferation, viability, cell cycle, migration, and invasion of U2OS cells. The effect was associated with Zn ions released into the culture medium during biocorrosion, which impede the proliferation of tumor cells by changing the cell cycle and inducing cell apoptosis, mediated changes in the mitochondrial membrane potential, and activation of the caspase cell cycle . In addition, the ability of these tumor cells to migrate into the tissue is diminished through the inhibition of mitogen‐activated protein kinase (MAPK) activation.…”
Section: Introductionmentioning
confidence: 99%